The Harvard Business Review Family Business Handbook - Baron, Josh; Lachenauer, Rob (Ascent Audio, 2021)
The one book you need to navigate the complex decisions and critical relationships necessary to create and sustain a healthy family business-and business family. Though "family business" may sound like it refers only to mom-and-pop shops, businesses owned by families are among the most significant and numerous in the world. But surprisingly few resources exist to help navigate the unique challenges you face when you share the executive suite, tax returns, and holidays. How do you make the right decisions, critical to the long-term survival of any business, with the added challenge of having to do so within the context of a family? This comprehensive handbook brings you sophisticated guidance and practical advice from family business experts Josh Baron and Rob Lachenauer. Based on their decades-long experience working closely with a wide range of family businesses around the world, the authors present proven methods and approaches
Online resource; Title from title page (viewed January 26, 2021)
Keywords: Livres numériques; Audiobooks